Analisis Kelayakan Finansial Ubi Kayu (Manihot esculenta) di Kecamatan Tlogowungu Kabupaten Pati - Rosinta, Maela; Ekowati, Titik; Setiadi, Agus (Universitas Galuh, 2026)
Financial feasibility analysis was conducted to evaluate the feasibility of cassava farming based on the financial performance of the business. This study aims to analyze income and financial feasibility as well as the sensitivity of changes in production factors and cassava yield in Tlogowungu District, Pati Regency. The research was carried out over four months, from April to July 2025, in Lahar Village, Tlogosari Village, Regaloh Village, Suwatu Village, and Cabak Village, Tlogowungu District, Pati Regency. The research method used was a survey method with a total sample of 70 cassava farmers, determined through simple random sampling. The research data were analyzed using descriptive quantitative analysis. Statistical data analysis was performed using Microsoft Excel and IBM SPSS statistical tests. The results of the study showed that the average cassava farm area was 2.45 ha, with productivity of 17,629 kg/ha, average production of 43,191 kg, and an average selling price of Rp1,844/kg. The total farming cost amounted to Rp33,892,956/ha/MT, while the revenue reached Rp82,381,143/ha/MT, and the income was Rp48,488,187/ha/MT. The EAT (Earnings After Tax) was Rp48,483,220/ha/MT, with a BEP (Break-Even Point) of 18,321 kg in units and Rp691/kg in currency value. The profitability ratio was 57.77%, indicating that cassava farming is profitable. The investment feasibility analysis showed a B/C ratio of 2.13, an NPV (including land investment) of -Rp265,933,808, and an NPV (excluding land investment) of Rp130,401,907, indicating that the farming enterprise is financially feasible. The IRR (Internal Rate of Return) was 293.65%, and the Payback Period (PP) was 35 months, which further confirms that cassava farming is feasible to operate. The sensitivity analysis revealed that a 10% increase in production costs, a 10% decrease in selling prices, and a combination of both cost increases and output decreases are sensitive to the financial feasibility of cassava farming.